Retro vesical solitary fibrous tumor: A case report - Mohamed Ali Bedoui; Ahmed Saadi; Bourgou Ibrahim; Seif Mokadem; Amine Hermi; Bilel Saïdani; Haroun Ayed; Marouene Chakroun; Riadh Ben Slama (Urology Case Reports)
Solitary fibrous tumor (SFTs), initially described in the 1930s, are a group of rare heterogeneous tumors primarily located in the pleural area but can manifest in any site.This article focuses on the case of a patient with a localized retroperitoneal pubic tumor treated surgically, which demonstrates on one hand the heterogeneity of clinical manifestations, the limited diagnostic contribution of imaging, and on the other hand the histological diagnostic difficulty despite the recent contribution of immunohistochemistry. Management remains primarily surgical, to the detriment of other alternatives that have not yet shown encouraging results.